In situ-produced 10Be and 26Al indirect dating of Elarmékora Earlier Stone Age artefacts: first attempt in a savannah forest mosaic in the middle Ogooué valley, Gabon. (25th April 2022) - Braucher, R.; Oslisly, R.; Mesfin, I.; Ntoutoume, P. P.; ,
Abstract : Discovered in 1988 by R. Oslisly and B. Peyrot, Elarmékora is a high terrace that, today, is situated 175 m above the Ogooué River in the historical complex of Elarmékora, attached to the Lopé National Park in Gabon, a World Heritage site since 2007. The site yielded a small lithic assemblage, including mainly cobble artefacts embedded within the 1 m thick alluvial material. Based on geomorphological and palaeoclimatological criteria, the preliminary dating suggested an age of 400 ka. However, Elarmékora could be a key site for Atlantic Central Africa if this lithic industry can be dated absolutely. In 2018 and 2019, two field trips were organized to collect surface samples as well as samples in vertical depth profiles with the aim of measuring their in situ -produced cosmogenic nuclide ( 10 Be and 26 Al) content. Results suggest a surface abandonment between 730 and 620 ka ago representing a minimum age for the cobble artefacts. Concurrently, technological reappraisal of the artefacts suggests an atypical lithic industry that should, for the moment, be considered as 'undiagnostic' Earlier Stone Age. This age bracketing may be compared with a similar age range obtained for prehistoric occupations in Angola using the same approach. This age will place Elarmékora among the oldest evidence for the presence of hominins in western Central Africa and raises the question of a 'West Side Story' to early human dispersals in Africa. This article is part of the theme issue 'Tropical forests in the deep human past'.